Bertahan Dalam Moderenisasi: Upaya Mempertahankan Nilai-Nilai Budaya Melalui Pengenalan Permainan Tradisional - Maulana Aditia, Ilham; Dinie Anggraeni Dewi; Rizky Saeful Hayat (PT. ALHAFI BERKAH INDONESIA, 2023)
In today's world, where the latest information technology and technology have facilitated the entry of foreign cultures, the decline of cultural values and national character is an unavoidable problem. The development of information technology and the internet has brought major changes in various fields of human life, including entertainment and recreation. One of the impacts that is very interesting to discuss is the loss of traditional games. Therefore, this research explains that there are student personality values that can be constructed through traditional games. This research uses a qualitative descriptive method. The development of increasingly sophisticated technology is an important means in achieving more effective and efficient educational goals. Therefore, it is necessary for educators to develop skills in utilizing technology and learning media.